Step-by-Step Training Video and Manual for the Physical Examination - Nelia Maria Afonso; Lawrence Roger Schwartz; Simone Brennan (Association of American Medical Colleges, 2011)
Abstract Because of sicker patients and shorter hospital stays, it has been increasingly difficult to secure hospitalized patients appropriate for teaching physical examination to medical students. Physicians are also under pressure to generate revenue, leaving less time for non-revenue-generating activities such as supervising medical students. To proactively address the above concerns, the course faculty at Wayne State University School of Medicine decided to implement a program of using standardized patients to supplement the teaching of physical diagnosis. This program lets students learn and practice their physical examination skills in a less stressful but more predictable and standardized environment, all the while providing them with individualized instruction. It also allows the students the ability to practice repeatedly and to obtain feedback from the standardized patient teaching associate about their technique. This resource features a comprehensive step-by-step guide, including a video and instructional materials, for teaching the basic physical exam. Since 2004, we have been using standardized patient teaching associates to help teach the physical exam to our preclinical medical students. These materials have been very effective in standardizing the teaching for our large medical school class. It has also allowed students to acquire basic physical exam skills by practicing on standardized patient teaching associates prior to their contact with real patients in the hospital setting. Trainees of other health care professions can also use this resource.